Safety of rapid injection of undiluted ferric carboxymaltose to patients with iron‐deficiency anaemia: a Phase II single‐arm study. Issue 8 (22nd August 2021) - Pasricha, Sant‐Rayn; Gilbertson, Michael; Indran, Tishya; Bennett, Ashwini; van Dam, Matthew; Coughlin, Elizabeth; Dev, Anouk; Chunilal, Sanjeev; Opat, Stephen
Abstract: Background: Ferric carboxymaltose is increasingly utilised to treat iron deficiency and is usually diluted in saline and administered as an intravenous infusion over 15 min. Although this is highly convenient compared with older formulations, we hypothesised the drug could be administered, safely given as a rapid bolus injection. Aims: To define the risk of serious adverse events following administration of an undiluted, rapid, high‐dose ferric carboxymaltose injection. Secondary aims included all other adverse events, as well as longitudinal effects on haemoglobin, iron stores, phosphate and hepcidin. Methods: In a single‐arm, Phase II study in 121 patients with iron‐deficiency anaemia, we administered up to 1000 mg of ferric carboxymaltose as a rapid undiluted bolus injection, and recorded adverse events and collected blood samples over the first hour, and again at 2 and 4 weeks post‐treatment. Results: No patient experienced a serious adverse event. Flushing during the injection was common, as was a transient headache in the subsequent weeks. One patient experienced Grade 3 chest tightness, necessitating emergency department assessment but not admission or treatment. Treatment produced an average 12.3 g/L improvement in haemoglobin within 2 weeks, but commonly caused reductions in serum phosphate (although none of these was clinically symptomatic). Parenteral iron caused elevations in hepcidin sustained to 4 weeks post‐injection. Patients stated they would be prepared to receive the treatment again. Conclusion: Rapid injection of undiluted ferric carboxymaltose is well tolerated and could provide an approach to treat patients in the ambulatory setting.